2016
DOI: 10.1371/journal.pone.0168948
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Performance of the Simplified Acute Physiology Score (SAPS) II and the Initial Sequential Organ Failure Assessment (SOFA) Score in Acutely Ill Intensive Care Patients: Post-Hoc Analyses of the SUP-ICU Inception Cohort Study

Abstract: PurposeSeverity scores including the Simplified Acute Physiology Score (SAPS) II and the Sequential Organ Failure Assessment (SOFA) score are used in intensive care units (ICUs) to assess disease severity, predict mortality and in research. We aimed to assess the predictive performance of SAPS II and the initial SOFA score for in-hospital and 90-day mortality in a contemporary international cohort.MethodsThis was a post-hoc study of the Stress Ulcer Prophylaxis in the Intensive Care Unit (SUP-ICU) inception co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 49 publications
(70 reference statements)
1
34
1
2
Order By: Relevance
“…Whether the lower performance of our score compared with more complex scores is due to the chosen outcome measure, simplicity of the model or a combination is not possible to assess from our data. However, in a recent study from our group, we found little difference in SAPS II's discrimination for in‐hospital vs. 90‐day mortality . Third, mortality prediction scores have been criticised for predicting the obvious; e.g.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Whether the lower performance of our score compared with more complex scores is due to the chosen outcome measure, simplicity of the model or a combination is not possible to assess from our data. However, in a recent study from our group, we found little difference in SAPS II's discrimination for in‐hospital vs. 90‐day mortality . Third, mortality prediction scores have been criticised for predicting the obvious; e.g.…”
Section: Discussionmentioning
confidence: 55%
“…Existing severity scores are time‐consuming and complex to use, and their interpretation is often hampered by missing data . Performance of SAPS II is similar to that of the more complex SAPS 3, and the Sequential Organ Failure Assessment (SOFA) score appears to be similar or only slightly inferior at discriminating between survivors and non‐survivors compared with SAPS II, despite being simpler and not developed for this purpose. Finally, severity score performance is affected by the choice of outcome .…”
mentioning
confidence: 99%
“…In the above mentioned and some other studies comparing the usefulness of scales, the values for SOFA ranged from 0.67 to 0.84 [6][7][8][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the SOFA score was not designed for mortality prediction but to evaluate organ dysfunction and morbidity. 33 On the other hand, the fact that just the APACHE II and the PSI system scores showed statistical differences highlights the hypothesis that mortality prediction may be related to prior health conditions. Apart from these two score systems, only the SAPS II takes prior health conditions into consideration and, although its results were not statistically significant, it was the third more accurate system predicting mortality.…”
Section: Discussionmentioning
confidence: 99%